The Technological Development of the Brewery in town Opava in the Years 1824–1945 - Starec, Milan (KVASNY PRUMYSL, 2017)
During period 1824–1826 was established an urban brewery in the town Opava (Tropau Silesia), in the middle of the 19. century had been introduced bottom fermenting, Soon after cancellation of propination law was introduced a steam engine. The modernization of the brewery was ongoing. At the turn of 19th and 20th centuries the brewery as a second biggest one in Silesia produced 80 000 hl yearly. After overcoming the consequences of the World War I. the brewmaster František Rosibal was in charge of modernization of the brewery, especially on the construction of the brew house and bottling cellar. Before the start of the World War II. the production capacity of the brewery was over 100 000 hl per year. The bombing in the year 1945 was the worst blow for the brewery.